Barriers to start the physical activity among seniors living in lesser Poland - Zdebska-Biziewska, Halina (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
Society of our civilization is aging. People are living longer and therefore the number of older people increases thus it becomes important not only a long life, but above all, the quality of life. The quality of life which depends mainly on care for health, physical activity including their lifestyles. Physical activity is seen as one of the most important factors of human health. This article aims at analysing the structure of physical activity among seniors living in Lesser Poland as well as the barriers of starting such activity. The research was conducted within the scope of the PolSenior nationwide programme, financed in the form of a grant by the Ministry of Science and Higher Education (ref. no. PBZ-MEIN-9/2/2006). The sample selection of respondents had a random character (of three-stage process). The study used some of the results – survey data of 157 men and 187 women of 65+ years of age, inhabitants of the province of Lesser Poland. The results were analysed in terms of the three age groups: 65–74, 75–84 and over 85 years; of age and gender, place of residence due to the number of inhabitants (20 thousand / over 20 thousand) as well as socio – professional status (blue-collar workers / non-physical workers). The most common barrier to start physical activity for seniors surveyed in the region are considerations of health and mental condition.